Social Media Marketing Strategy of Indonesian Tourism in The Time of Pandemic - Chloridiany, Aulia (E-Journal of Tourism; Volume 8 Number 1 (March 2021)DO - 10.24922/eot.v8i1.71445, 2021)
Tourism is among one of the hardest hit sectors caused by the Covid-19 pandemic. According to UNWTO (2020), 100-120 million direct tourism jobs were at risk and international tourist numbers in January – May 2020 decreased 56% year on year. Indonesia’s tourism sector is not an exception. The number of foreign tourist visits to Indonesia fell down -89.22 % year on year, which definitely affects the whole condition of Indonesian tourism. Therefore, the Indonesian government have done several efforts to manage the situation since the pandemic started. Due to limitation of offline activities, digital marketing, including social media, had become the main strategy to maintain Indonesian tourism’s presence in the market. This paper will discuss the social media marketing strategy has been done by the Ministry of Tourism and Creative Economy (MOTCE) Indonesia to promote Indonesian tourism during pandemic time, especially for the global market. Using social media marketing strategy (SMMS) framework from Li, Larimo and Leonidou (2020), this research found that the social marketing media strategy has been implemented by MOTCE could be categorized as the social content strategy, as the Indonesia Travel accounts focus on suitable contents with the audiences who struggle with the pandemic. Indonesia Travel as the official social media marketing accounts, has been active to post contents even since the beginning of the pandemic through Facebook, Instagram, Twitter, Youtube, Weibo, and Wechat. From January to September 2020, Indonesia Travel posted more than 683 contents. However, the pandemic has driven the Indonesia Travel accounts to slightly changed the marketing objectives, adapting with what audiences wanted. Not only posting about the beauty of tourism destinations in Indonesia, since February they also post about Covid-19 related information.